2015
DOI: 10.4028/www.scientific.net/amr.1112.180
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Performance of Copper-Modified Titanium Dioxide Prepared by UV Reduction Method

Abstract: In the present study, commercial Hombikat N100 TiO2 that consists of 100% of anatase phase was modified with copper (Cu) as a co-catalyst via two different preparation methods, which were photocatalytic UV reduction and impregnation methods. The Cu loading was fixed to be 0.1 wt%. The X-ray diffraction (XRD) patterns showed that Cu/TiO2 sample prepared via different preparation methods gave different crystallinity and/or crystallite size. The Cu/TiO2 sample prepared by photocatalytic UV reduction method has lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Recently, the photodeposition method has been proposed as a suitable method to directly investigate the role of added copper or lanthanum species without such heat-treatment effects [ 20 21 ]. Moreover, the modification of TiO 2 nanoparticles by photodeposition resulted in an improved photocatalytic activity as compared to unmodified TiO 2 [ 20 22 ]. Therefore, it is meaningful to employ the photodeposition method to prepare Fe 2 O 3 /TiO 2 catalysts without heat treatment at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the photodeposition method has been proposed as a suitable method to directly investigate the role of added copper or lanthanum species without such heat-treatment effects [ 20 21 ]. Moreover, the modification of TiO 2 nanoparticles by photodeposition resulted in an improved photocatalytic activity as compared to unmodified TiO 2 [ 20 22 ]. Therefore, it is meaningful to employ the photodeposition method to prepare Fe 2 O 3 /TiO 2 catalysts without heat treatment at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive exposure of 2,4-D leads to adverse impacts on the ecosystem, and thus, the toxic organic pollutant must be eliminated from the water source utilizing efficient approaches. Various removal methods of 2,4-D have been developed, including adsorption [ 24 ], biodegradation [ 25 ], ozonation [ 26 ], and photocatalytic degradation [ 15 , 20 22 27 32 ], of which the latter has been recognized for its capability to decompose the organic pollutant under a mild environment. In the present work, it was shown that the different preparation methods resulted in distinctly different properties and photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to improve the activity of TiO 2 photocatalyst for degradation of 2,4-D is by introducing transition metal and rare earth oxides, such as copper [5][6][7][8], lanthanum [9][10], and iron oxides [11]. In particular, it has been shown that cobalt species has the potential of enhancing the photocatalytic activity of TiO 2 for various reactions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficient treatment to remove 2,4-D in water still needs to be investigated. There are various methods that have been reported to degrade 2,4-D. One of the most promising methods is by photocatalytic reaction [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation